Pelaksanaan Pembelajaran Seni Budaya Musik Tradisional (Talempong Pacik) Siswa Kelas VIII-1 SMP Negeri 43 Padang - Afrialdo Sardova; Syeilendra Syeilendra (Universitas Palangka Raya, 2024)
. This study aims to describe the process of implementing Talempong Pacik Music learning in grades VIII-1 at SMP Negeri 43 Padang. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery and cameras. This research data uses primary data and secondary data. Data are collected through literature study, observation, interviews, documentation. The steps of analyzing data are data classification, analyzing data, and inferring data. The results showed that the implementation of learning Traditional Music Culture Arts (Talempong Pacik) in Grades VIII-1 SMP Negeri 43 Padang consisted of 4 meetings, namely initial activities, core activities and closing activities. The scores of students after the implementation of Traditional Music Culture (Talempong Pacik) learning activities are still many who have not reached KKM, there are 15 students who have not reached KKM and 8 students can only achieve predetermined KKM standard scores and there are 9 students who get scores that exceed KKM. The learning process has not fully obtained satisfactory learning results. Teacher limitations in using teaching aids and limited time in practical activities, teachers continue to try to motivate students, so that students continue to be enthusiastic in the process of learning activities, students still look rigid in carrying out learning activities including in the process of traditional music learner practice activities, so that there are still many student scores below KKM, and the rest only reach the KKM limit. So it is known that students have not received maximum grade results.